Salient Studies of Signed Language Interpreting in the Context of Community Interpreting Scholarship - Metzger, Melanie (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
During the pastfour decades, signed language interpreting (SLI) scholars have created a growing body of research. This work covers a broad range of topics, from a psycholinguistic perspective to a sociolinguistic one, from analyses of the cognitive processes in which signed language interpreters engage, to analyses of the management and participation framework of interpreted events, from linguistically-oriented studies to studiesfocused on aspects of the environment in particular settings or various applications of the interpreting process that impact on the flow and outcome of the interpreted event, be it consecutive or simultaneous work, in-person or via technology. Yet these contributions to our understanding of SLI neither occur in a vacuum, nor do they reflect issues limited to SL interpreters. This paper examines seminal studies in SLI research, and contextualizes them within the largerframework of community interpreting research.